WISATA BAHARI PADA ZONA PEMANFAATAN TAMAN NASIONAL MANUSELA: POTENSI DAN FAKTOR PENGARUH PENGEMBANGAN - Kaya, Ivonne R. G.; Lima, Fildo de (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2018)
Tourism has become one of the major players in ?international commerce and represents one of the main income ?sources for many developing countries at the same time. These dynamics have turned tourism into a key driver for socio-?economic progress.? This article described the potential of tourism attraction and factor affecting the development of marine tourism area in the utilization zone of Manusela National Park. Semi-structured interviews, in-depth interviews and participant observations were conducted with respondent (n=110) in Bellarizky, Air Belanda, Ora Beach and Lizar Bahari resort. The potential of tourist attractions in the utilization zone of Manusela National Park is as a snorkeling, diving and point of view. Factors affecting the development are service, transportation, supporting facilities and tourism attractions.